Efficiency Performance of China Brand Automobiles: The Role of Innovation Systems - Jianglin, Jiang; Rossazana, Ab Rahim; Rosita, Hamdan (Innovative Information Science & Technology Research Group (ISYOU), 2025)
This research aims to examine and investigate the efficiency performance and its influencing factors of China brand automobiles’ innovation system using both theoretical and empirical approaches. Initially, the study applies the DEA model to assess the technical efficiency, pure technical efficiency, and scale efficiency of the innovation system of China brand automobiles. The results reveal a general upward trend in the innovation system’s efficiency of China brand automobiles. Subsequently, a panel regression model is employed to analyze the determinants impacting the efficiency of the innovation system. The findings of the research suggest that economic development, openness to international markets, and marketization enhance the technical efficiency of the innovation system of the domestic automobile industry. However, an increase in enterprise size tends to negatively affect this technical efficiency. While economic growth, openness, and marketization positively impact pure technical efficiency, the expansion of enterprise size exerts a detrimental effect. Conversely, enterprise size growth positively influences scale efficiency, whereas openness and marketization present some negative implications. Lastly, this study proposes policy recommendations from both governmental and enterprise viewpoints, aimed at promoting the sustainable advancement of the automobile industry.